Severe Omphalocele, Exstrophy of The Cloaca, Imperforate Anus, and Spinal Defects (Oeis) : A Case Report - Fahreza L Nasution; Noviardi Noviardi; Sofyan Andri; Dhini Ayulie Novri; Akbar Husaini Angkat (Universitas Malahayati, 2026)
ABSTRACT The OEIS complex—comprising Omphalocele, Exstrophy of the cloaca, Imperforate anus, and Spinal defects—is one of the rarest and most severe congenital malformation syndromes, with an estimated incidence of 1 in 200,000–400,000 live births. Early prenatal detection plays a critical role in facilitating appropriate counseling and multidisciplinary perinatal planning. We report a prenatally diagnosed case of severe OEIS complex in a 21-year-old primiparous woman referred for suspected abdominal wall defect and fetal tachycardia. Ultrasound revealed a single live fetus at 32 weeks' gestation with a large omphalocele, protruding bowel loops, and features suggestive of cloacal exstrophy. Postnatal examination confirmed omphalocele, cloacal exstrophy, imperforate anus, ambiguous genitalia, and right-sided congenital talipes equinovarus. These findings were consistent with the classical presentation of severe OEIS. This case underscores the importance of early prenatal diagnosis and coordinated multidisciplinary management in severe OEIS complex. Timely recognition through imaging and delivery planning at a tertiary care center are crucial for optimizing immediate neonatal outcomes. Long-term prognosis remains dependent on the extent of anomalies and access to comprehensive surgical and supportive care. Keywords: OEIS, Omphalocele, Exstrophy of the Cloaca, Imperforate Anus, and Spinal Defects, Ccongenital Anomaly.